The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1415-47572008000400012
|View full text |Cite
|
Sign up to set email alerts
|

Test-day milk yield as a selection criterion for dairy buffaloes (Bubalus bubalis Artiodactyla, Bovidae)

Abstract: Due to the great demand for buffalo milk by-products the interest in technical-scientific information about this species is increasing. Our objective was to propose selection criteria for milk yield in buffaloes based on total milk yield, 305-day milk yield (M305), and test-day milk yield. A total of 3,888 lactations from 1,630 Murrah (Bubalus bubalis) cows recorded between 1987 and 2001, from 10 herds in the State of São Paulo, Brazil, were analyzed. Covariance components were obtained using the restricted ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
33
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 11 publications
14
33
3
1
Order By: Relevance
“…Similarly, Ramos et al (2006), Tonhati et al (2008) and Rodrigues et al (2010) reported heritabilities of 0.21, 0.19 and 0.25 using REML on the same breed. In contrast, much higher variability (0.39) was reported by Araújo et al (2008) using BI suggesting that there is considerable genetic variability in this breed with a high potential of genetic gain for milk yield through selection.…”
Section: Resultsmentioning
confidence: 79%
“…Similarly, Ramos et al (2006), Tonhati et al (2008) and Rodrigues et al (2010) reported heritabilities of 0.21, 0.19 and 0.25 using REML on the same breed. In contrast, much higher variability (0.39) was reported by Araújo et al (2008) using BI suggesting that there is considerable genetic variability in this breed with a high potential of genetic gain for milk yield through selection.…”
Section: Resultsmentioning
confidence: 79%
“…In 2007, worldwide buffalo and cow milk productions were 85 and 560 million tonnes, respectively (FAO 2009). In the last decades, the Brazilian buffalo milk yield per lactation has significantly increased from 717.3 kg in 1995 (Tonhati et al 1996) to 1 650.0 kg in recent years (Ramos et al 2006, Tonhati et al 2008. This is mainly a consequence of the improvement in management, infrastructure and feeding practices on buffalo farms (Malhado et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For test-day yields, the heritability estimates ranged from 0.12 to 0.30, with the highest values being observed up to the third test month, followed by a decline until the end of lactation. The present results show that test-day milk yield, mainly during the first six months of lactation, could be adopted as a selection criterion to increase total milk yield (Tonhati et al 2008). Table 3.…”
Section: Modelsmentioning
confidence: 67%
“…Probably, this pattern is due to the fact that only more persistent cows remain producing until the tenth month of lactation which would decrease genetic variability (Tonhati et al 2008). …”
Section: Sire By Herd Interactionmentioning
confidence: 99%